LncRNAs in adaptive immunity: role in physiological and pathological conditions - Zeni, Pedro Faria; Mraz, Marek (RNA biology, 2021)
The adaptive immune system is responsible for generating immunological response and immunological memory. Regulation of adaptive immunity including B cell and T cell biology was mainly understood from the protein and microRNA perspective. However, long non-coding RNAs (lncRNAs) are an emerging class of non-coding RNAs (ncRNAs) that influence key factors in lymphocyte biology such as NOTCH, PAX5, MYC and EZH2. LncRNAs were described to modulate lymphocyte activation by regulating pathways such as NFAT, NFκB, MYC, interferon and TCR/BCR signalling (NRON, NKILA, BCALM, GAS5, PVT1), and cell effector functions (IFNG-AS1, TH2-LCR). Here we review lncRNA involvement in adaptive immunity and the implications for autoimmune diseases (multiple sclerosis, inflammatory bowel disease, rheumatoid arthritis) and T/B cell leukaemias and lymphomas (CLL, MCL, DLBCL, T-ALL). It is becoming clear that lncRNAs are important in adaptive immune response and provide new insights into its orchestration.
Keywords: aktivace lymfocytů; T-lymfocyty; Disease; signální transdukce; RNA dlouhá nekódující; Adaptive Immunity; Lymphocyte Activation; nemoc; T-Lymphocytes; Animals; lidé; RNA, Long Noncoding; Humans; zvířata; adaptivní imunita; Signal Transduction